P01.06 Spatially-resolved, highly multiplexed biomarker analysis of cancerous and normal human breast tissues. (1st October 2020) - Braubach, O; Basak, S; Gallina, M; Lee, W; Kim, J; Hempel, C; Williams, E; Shang, O; Cheung, B; Kennedy-Darling, J
Abstract : Background: Breast cancer has a high incidence rate and there is a need to develop new diagnostic tools and treatment regimens. Progress has, unfortunately, been slow and new technologies are urgently needed to generate a comprehensive understanding of breast cancer biology. Highly multiplexed imaging is an emerging tool that can help to unravel the complexities of the tumor microenvironment. This technology enables the detection of tens of biomarkers within a tissue specimen, and allows comprehensive cell phenotyping, biomarker quantification and spatial localization at cellular resolution. Such measurements can, in turn, provide insights into disease mechanisms and identify potential treatment targets. We demonstrate the development of a breast cancer specific CO-Detection by indEXing (CODEX ® ) panel that allows simultaneous in situ imaging of more than 30+ antibody markers. Materials and Methods: CODEX ® relies on a DNA-based tagging approach, whereby antibodies are labeled with specific oligonucleotide tags (barcodes) and dye-oligonucleotides (reporters) are iteratively hybridized and dehybridized across multiple cycles. This process is completely automated through the CODEX ® instrument and readily deployable on commercially available fluorescence microscopy systems. Using a 30+ antibody CODEX ® panel, we compared formalin-fixed paraffin embedded (FFPE) human breast cancer tissues at different stages of disease progression with normal breast tissues. Our antibody panel was designed to detect cancer cells as well as non-malignant cells in order to comprehensively survey the tumor microenvironment and normal control tissues. Data were analyzed using the CODEX ® software suite to identify key cell types and analyze spatial associations. Results: Our analyses revealed more than 20 distinct cell types in human breast cancer and normal tissues. Cell populations, biomarker expression and cellular spatial distributions differed distinctly between cancerous and normal breast tissues. Differences were robust, repeatedly observed and indicative of altered cellular milieus in normal versus cancerous breast tissues. Conclusions: Collectively, these data establish CODEX ® as a readily deployable and practical tool for spatially-resolved, highly multiplexed biomarker analysis of human FFPE samples. Disclosure Information: O. Braubach: A. Employment (full or part-time); Significant; Akoya Biosciences. S. Basak: A. Employment (full or part-time); Significant; Akoya Biosciences. M. Gallina: A. Employment (full or part-time); Significant; Akoya Biosciences. W. Lee: A. Employment (full or part-time); Significant; Akoya Biosciences. J. Kim: A. Employment (full or part-time); Significant; Akoya Biosciences. C. Hempel: A. Employment (full or part-time); Significant; Akoya Biosciences. E. Williams: A. Employment (full or part-time); Significant; Akoya Biosciences. O. Shang: A. Employment (full or part-time); Significant; Akoya Biosciences. B. Cheung: A. Employment (full or part-time); Significant; Akoya Biosciences. J. Kennedy-Darling: A. Employment (full or part-time); Significant; Akoya Biosciences.